Typology and Ideology: Moisei Ginzburg Revisited. (2nd April 2016) - Carpov, Victor; Lodder, Christina
Abstract: The typological theories articulated by Moisei Ginzburg and the architects of his circle guided the development of Soviet architecture and remain influential in Russia today. Re-visiting these ideas highlights their relationships to the concepts and theoretical principles that were elaborated by the academic schools, which were grounded in the traditions of the past. Recent historical studies have revealed this intimate connection between the academic tradition and the modernism that was born to negate it, emphasizing continuity in the historical path of architecture. Applied to the history of Soviet architecture, this insight does not raise questions about the nuances in stylistic or theoretical similarities or differences between Soviet constructivism and modernism, but rather between those ideological links that form two branches of one integral current in the evolution of twentieth-century architecture.